3(-5x-3)=-99

Simple and best practice solution for 3(-5x-3)=-99 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(-5x-3)=-99 equation:


Simplifying
3(-5x + -3) = -99

Reorder the terms:
3(-3 + -5x) = -99
(-3 * 3 + -5x * 3) = -99
(-9 + -15x) = -99

Solving
-9 + -15x = -99

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9' to each side of the equation.
-9 + 9 + -15x = -99 + 9

Combine like terms: -9 + 9 = 0
0 + -15x = -99 + 9
-15x = -99 + 9

Combine like terms: -99 + 9 = -90
-15x = -90

Divide each side by '-15'.
x = 6

Simplifying
x = 6

See similar equations:

| x^2+4y^2-10x-32y+85=0 | | z=3z-70 | | 75/15=x/14 | | n-5/1 | | 3q=8q-65 | | 5a+6y=37 | | 6x-3(x+4)=-36 | | 2.25t+5=13.5 | | x^4-3x^3-8x^2-6x-20=0 | | x^2-xy+3y=0 | | x+(-6)+10= | | 24=-2(4x+4) | | 5z=z+44 | | 3x+4y+2x-9y= | | Y=e^5*x | | 18+3v=14 | | =e^5x | | 5m+3t-4m-t= | | 2x-1=x^2 | | -15=w/3-10 | | (1/2)7=1/64 | | kx^2+(k+3)x+4=0 | | 112-y=244 | | 18+6=48 | | 15t=4000 | | 5x+2=625 | | (2x+-3)(4x+-5)=0 | | -4(3x-3)=48 | | 1-7x=36 | | 2-2x=-1-3x | | x^3+2x^2+100x=0 | | (2x^3+5x^2+7x+1)=0 |

Equations solver categories